Bug boys - Knetzger, Laura, 1990-; Lynde, Lyle (New York : RH Graphic, 2020)
Follows two bug friends, Stag-B and Rhino-B, as they explore their world and share adventures.
"Originally published in the United States in black and white and in different form by Czap Books, Providence, Rhode Island, in 2015."
"A Junior Library Guild Selection"--Back cover.
Keywords: Graphic novels; Graphic novels; Insects -- Fiction; Adventure and adventurers -- Fiction; Best friends -- Fiction; Friendship -- Fiction